The Enhanced Single-dish Control System and wide surveys of compact sources - Righini, Simona <1976> (Alma Mater Studiorum - Università di Bologna, 2010)

(untitled)
The Italian radio telescopes currently undergo a major upgrade period in response to the growing demand for deep radio observations, such as surveys on large sky areas or observations of vast samples of compact radio sources. The optimised employment of the Italian antennas, at first constructed mainly for VLBI activities and provided with a control system (FS – Field System) not tailored to single-dish observations, required important modifications in particular of the guiding software and data acquisition system. The production of a completely new control system called ESCS (Enhanced Single-dish Control System) for the Medicina dish started in 2007, in synergy with the software development for the forthcoming Sardinia Radio Telescope (SRT). The aim is to produce a system optimised for single-dish observations in continuum, spectrometry and polarimetry. ESCS is also planned to be installed at the Noto site. A substantial part of this thesis work consisted in designing and developing subsystems within ESCS, in order to provide this software with tools to carry out large maps, spanning from the implementation of On-The-Fly fast scans (following both conventional and innovative observing strategies) to the production of single-dish standard output files and the realisation of tools for the quick-look of the acquired data. The test period coincided with the commissioning phase for two devices temporarily installed – while waiting for the SRT to be completed – on the Medicina antenna: a 18-26 GHz 7-feed receiver and the 14-channel analogue backend developed for its use. It is worth stressing that it is the only K-band multi-feed receiver at present available worldwide. The commissioning of the overall hardware/software system constituted a considerable section of the thesis work. Tests were led in order to verify the system stability and its capabilities, down to sensitivity levels which had never been reached in Medicina using the previous observing techniques and hardware devices. The aim was also to assess the scientific potential of the multi-feed receiver for the production of wide maps, exploiting its temporary availability on a mid-sized antenna. Dishes like the 32-m antennas at Medicina and Noto, in fact, offer the best conditions for large-area surveys, especially at high frequencies, as they provide a suited compromise between sufficiently large beam sizes to cover quickly large areas of the sky (typical of small-sized telescopes) and sensitivity (typical of large-sized telescopes). The KNoWS (K-band Northern Wide Survey) project is aimed at the realisation of a full-northern-sky survey at 21 GHz; its pilot observations, performed using the new ESCS tools and a peculiar observing strategy, constituted an ideal test-bed for ESCS itself and for the multi-feed/backend system. The KNoWS group, which I am part of, supported the commissioning activities also providing map-making and source-extraction tools, in order to complete the necessary data reduction pipeline and assess the general system scientific capabilities. The K-band observations, which were carried out in several sessions along the December 2008-March 2010 period, were accompanied by the realisation of a 5 GHz test survey during the summertime, which is not suitable for high-frequency observations. This activity was conceived in order to check the new analogue backend separately from the multi-feed receiver, and to simultaneously produce original scientific data (the 6-cm Medicina Survey, 6MS, a polar cap survey to complete PMN-GB6 and provide an all-sky coverage at 5 GHz).